2020
DOI: 10.4236/ojped.2020.101024
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hypoglycemia in Hospitalized Children with Diabetic Ketoacidosis in Brazzaville

Abstract: Background: Severe hypoglycemia is a lifethreatening iatrogenic complication in the management of diabetic ketoacidosis, however, few studies have described how often this complication occurs. Objective: To identify the risk factors for severe hypoglycemia in children treated for diabetic ketoacidosis and to describe the sociodemographic, clinical characteristics and outcome of these children. Methods: From January 2013 to December 2017, 69 children admitted to pediatric intensive care unit with a diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…The elevation of these markers indicates functional renal failure and can specify the severity of ketoacidosis and guide therapeutic management. The studies of Sanogo showed similar results in Bamako [13].…”
Section: Discussionsupporting
confidence: 68%
“…The elevation of these markers indicates functional renal failure and can specify the severity of ketoacidosis and guide therapeutic management. The studies of Sanogo showed similar results in Bamako [13].…”
Section: Discussionsupporting
confidence: 68%